Wpływ wieku rolników na ich zachowania produkcyjne w okresie transformacji systemowej w Polsce - Klepacki, Bogdan (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 1996)
In the paper there are presented the result of research devoted the behaviour of farmers in time of general changes in Polish economy. An author stated that farmers age is one of important factors influenced on their production decisions. The younger person were better educated, have bigger acreage of land and often bay additional area, their farms were better equipment and often invested in new machinery and buildings. In the research was stated that young farmers have made changes characterised by active forms, expansion. Decisions the older farmers were more passive. That's mine that the quicker changes of possessors of farms could made development of agriculture more possible.